Influence of rumen bypass fat fed in a range supplement on the performance of cows and calves grazing bluestem range - L. Corah; B. Cochran; D. Harmon; T. Goehring (Kansas Agricultural Experiment Station Research Reports, 1987)
Adding rumen bypass fat to a range supplement reproductive characteristics, cow weight and condition performance during a 43-day postpartum feeding period.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Rumen; Performance; Bluestem